Needs assessment to promote the digital literacy among students in Thai community colleges - Anyamanee Ussarn; Paitoon Pimdee; Thiyaporn Kantathanawat (International Journal of Evaluation and Research in Education (IJERE), 2022)
The objective of this research was to assess the need to promote digital literacy of the students under the supervision of Tak Community College. The population consisted of 152 students in Tak Community College, Tak Province, Thailand, registered for the second semester of the 2020 academic year. The research instrument was a digital literacy questionnaire, and the data were analyzed using percentage, mean, standard deviation, and the prioritization of the need. The findings revealed that the level of digital literacy skills of the students was moderate. The level of digital literacy that students expected, however, was very high. In concluding remarks, it was found that the highest average of the digital literacy skills of the Tak Community College students was the use of the spreadsheet program (PNIModified=0.30), followed by the use of presentation program (PNIModified=0.27), and the word processor program as the lowest average point of skills (PNIModified=0.23). The students of Tak Community College, therefore, are inevitability required the better digital literacy skills development from the lessons enlightened by the teachers.